Heart Failure in Adult Congenital Heart Disease (Congenital Heart Disease in Adolescents and Adults,, 2018)
This book sheds new light on the diagnosis and treatment of Heart Failure in adult patients with congenital heart disease. This is a rapidly growing clinical issue for this group of patients and the clinical teams caring for them. The book highlights the major clinical dilemmas in diagnosing heart failure in patients with a lifelong cardiac condition and describes in details the utility of biomarkers, complex imaging and functional tests, e.g. the cardiopulmonary exercise testing. A step-wise approach to treatment is described from drug therapy through to devices and transplantation. As such, the book offers an essential guide for cardiologists and cardiac surgeons looking to optimize the management of patients with delicate physiology and complex disease.